La revolución en crisis : la aventura del maximato - Córdova, Arnaldo (Cal y Arena, 1995)
"Important study of the Maximato (1928-34) sees Cardenismo as the culmination of - rather than the replacement for - many important political developments under Calles. Concludes that there were 'important differences' but also 'essential overlaps' between Calles and Cárdenas. Cardenismo would not have been possible without the Maximato"-- Handbook of Latin American Studies, v. 58.